ON ONE NONLINEAR DIFFERENTIAL SEVERAL PERSON GAME IN CASE OF MANY AIM SETS - Stepanyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
The differential several person game in case of aim sets is considered, the dynamics of which is described by a nonlinear differential equation. A balance set of strategies is constructed by means of the method of extreme aiming at the corresponding set.
Keywords: differential several person games; many aim sets; balance set of strategies